If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 5(x + 3) Reorder the terms: 23 = 5(3 + x) 23 = (3 * 5 + x * 5) 23 = (15 + 5x) Solving 23 = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 23 + -5x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 23 + -5x = 15 + 0 23 + -5x = 15 Add '-23' to each side of the equation. 23 + -23 + -5x = 15 + -23 Combine like terms: 23 + -23 = 0 0 + -5x = 15 + -23 -5x = 15 + -23 Combine like terms: 15 + -23 = -8 -5x = -8 Divide each side by '-5'. x = 1.6 Simplifying x = 1.6
| 4lg(x)-6=2lg(x) | | gx=144 | | (x+1)(x-2)=(x-1)(x-1) | | -5/6=3/4n | | (3x-1)/(x-4)=0 | | 5x-8=3x-11+8 | | 2z-12-1=z-25+z | | 3/1728 | | 6(-2-3x)+8= | | -x-4=3x+6 | | -3-3x/21 | | 2(3m-9)-3(m-2)= | | 4x+5=8x+5 | | 7x-2=9x-4 | | 9x-9=19x-19 | | 11x-12=13x-20 | | 6x+3y=153 | | x+y=1.23 | | 5-x=32 | | 2x+15=13x+1 | | 10x+(12-x)=9x+12 | | 5x-1=10x-17 | | 19x+2=3x+14 | | 10/x=6.3681 | | 4.6/y=44.16 | | -32*Y=-22336 | | 10y+15x=5 | | (12-x)+x=12+36 | | (12-x)+x=12 | | 143=6x+17 | | 5(2y+4)=24 | | 8x+7=7x-3 |